(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Despite high pressure of population on land and other natural resources, Bangladesh has made remarkable progress in food production over the last three and a half decades. The shrinking trend in land availability for crop production is another challenge ahead of the economy. The declining trend in cultivable land was quite sharp in the period of 1990 to 2005. Although the population has doubled, cereal food production has increased in the range of 100-125% during this period. The progress is the result of development and dissemination of modern high-yielding rice and wheat varieties supported by favourable public policies. There has been impressive technological advancement in the rice sector. Bangladesh Rice Research Institute (BRRI) made substantial contribution in the recent past and a total of 59 modern high yielding rice varieties (HYVs) suitable for different production ecologies have been released after independence in 1972. Although the progress in variety development was slower during the seventies and eightees, it was triggered up in the later decades and a quantum of achievement was made after 2000. The rate of varietal development was almost double in the last quarter of the decades compared to that made in the seventees. During the period of 1972 to 1980, the share of modern rice in total production was only 29%, but by the year 1985, it increased to 41% and jumped to nearly 90% by 2010 implying a highly impressive contribution of the diffusion of modern rice technologies in the overall supply of cereal foods in the country. Bangladesh J. Agril. Res. 38(2): 257-269, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15889